The Wiley handbook of anxiety disorders - Emmelkamp, Paul M. G., 1949-; Ehring, Thomas, 1973- (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2014)
'This two-volume, state-of-the-art Handbook on the research and treatment of anxiety and related disorders is the most internationally and clinically oriented Handbook currently available, encompassing a broad network of researchers, from leading experts in the field to rising stars. The very first handbook to cover anxiety disorders according to the new DSM-5 criteria Published in two volumes, the International Handbook provides the most wide-ranging treatment of the state-of-the-art research in the anxiety disorders Offers a truly international aspect, including authors from different continents and covering issues of relevance to non-Western countries Includes discussion of the latest treatments, including work on persistence of compulsions, virtual reality exposure therapy, cognitive bias modification, cognitive enhancers, and imagery rescripting Covers treatment failures, transdiagnostic approaches, and includes treatment issues for children as well as the older population Edited by leaders in the field, responsible for some of the most important advances in our understanding and treatment of anxiety disorders'--
'This state-of-the-art Handbook on the research and treatment of anxiety and related disorders is the most clinically-oriented Handbook currently available'--
Volume I. Theory and research -- volume II. Clinical assesment and treatment.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Clinical psychology -- Handbooks, manuals, etc; Psychology, Clinical; Anxiety -- Handbooks, manuals, etc; Anxiety Disorders; PSYCHOLOGY -- Clinical Psychology; Clinical psychology; Handbooks; Electronic books; Handbooks and manuals